ANALISIS PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP KINERJA PENGELOLAAN DANA BOS DI SDN 11 SENDANU DARULIHSAN - Fauzan Haqiqi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
SDN 11 Sendanu Darulihsan is a basic level formal education provider located in Sendanu Darulihsan village, Tebing Tinggi Timur sub-district, Meranti Islands district, Riaun Province. This study aims to determine the significant influence between transparency and accountability both partially and simultaneously on the performance of BOS funds management at SDN 11 Sendanu Darulihsan, with 2 independent variables (X1 and X2) and 1 dependent variable (Y), this study uses quantitative methods using primary data. The population in this study was a student guardian of SDN 11 Sendanu Darulihsan which amounted to 35 people, with a sample of 32 research samples. The data analysis technique used is multiple linear regression analysis, using processed data in the form of program SPSS 23.0. The results of this study indicate that partially the Transparency variable (x1) does not have a significant influence on the Performance of BOS Fund Management variable (Y) at SDN 11 Sendanu Darulihsan and the Accountability variable (X2) has a significant influence on the Performance of BOS Fund Management variable (Y) at SDN 11 Sendanu Darulihsan. That simultaneously the Transparency variable (X1) and Accountability variable (X2) have a significant influence on the Performance of BOS Fund Management variable (Y) at SDN 11 Sendanu Darulihsan